SAT0645 Magnetic resonance imaging and histopathological correlation in dermatomyositis. (15th June 2017) - Collado, MV; Milisenda, JC; Tomás, X; García, AI; Faruch, M; Grau, JM; ,
Abstract : Background: Dermatomyositis represents one of the major forms among the inflammatory myopathies (IIM). Although the muscle biopsy remains the definitive test, MRI has been used to detect unique patterns of muscle involvement. To date, no studies have compared MRI with muscle pathology in naïve DM. Objectives: To compare the pattern of muscle MRI with muscle pathology. Methods: All the patients enrolled in the Hospital Clínic de Barcelona (HCB) from January 2009 to December 2016 with an available MRI, performed just before muscle biopsy were included. The HCB ethics committee approved this study, and written informed consent was obtained from each participant. MRI data and the clinical and demographic features were prospectively collected. Patients were classified as having definite DM (ref 4). MRI was performed on a 1.5T with standardized protocol of whole body or scapular and pelvic girdle MRI, which include coronal and axial T1-weighted and STIR images. Image analysis was performed by two experienced musculoskeletal radiologists masked to the disease activity. The presence of oedema, fatty replacement and fascial oedema was evaluated in the biopsied muscle. Muscle and fascial inflammation was scored using a 0–3 point scale. The extent of muscle involvement was also evaluated by the analysis of 12 to 14 axial images and a percentage of muscle volume was calculated. Fatty replacement was scored using a 0–3 point scale. Muscle biopsies were evaluated by two trained pathologists at the HCB. Muscle biopsies were routinely processed. Quantification of fiber necrosis, regeneration and inflammation infiltrate were recorded. All statistical analyses were performed using "SPSS v22.0 ®". In all statistical tests performed p value of 0.05 was considered significant. Results: A total of 16 (13 female) patients were included. Except in one patient all of them had proximal muscle weakness, and all of them except one had typical DM skin lesions. In 12% of the patients a solid cancer was diagnosed. All patients had fascial edema at muscle MRI while no one had fatty replacement, and 65% had muscle oedema. Only one biopsy was normal. A significant correlation was found between muscle inflammation and MRI muscle edema (p=0, 036) and the percentage of volume muscle involvement at MRI (p=0, 027). Muscle necrosis was seen in those patients with moderate and severe fascial edema compared with those with mild fascial edema (p=0, 032). More regenerating cells were seen in those patients with moderate and severe muscle edema compared with negative or mild muscle oedema (p=0, 018). Conclusions: A strong and significant correlation between histological and imaging findings was found. Fascial and muscle edema were the predominant findings in DM patients References: Garcia J. MRI in inflammatory myopathies. Skeletal Radiol 2000;29:425–38. Connor A, Stebbings S, Hung N, et al. STIR MRI to Direct Muscle Biopsy in Suspected Idiopathic Inflammatory Myopathy. J Clin Rheumatol 2007;13: 341–45. Dalakas MC. Inflammatory muscle diseases. N Engl J Med 2015;373:393–4. Hoogendijk JE, Amato AA, Lecky BR, et al. 119th ENMC international workshop: trial design in adult idiopathic inflammatory myopathies, with the exception of inclusion body myositis, 10–12 October 2003, Naarden, the Netherlands. Neuromuscul Disord 2004;14:337–45. Disclosure of Interest: None declared